Improved MR phase-contrast velocimetry using a novel nine-point balanced motion-encoding scheme with increased robustness to eddy current effects - Espe, E; Espe, E; Aronsen, J; Aronsen, J; Aronsen, J; Skrbic, B; Skrbic, B; Skulberg, V; Schneider, J; Sejersted, O; Sejersted, O; Zhang, L; et al. (2013)
Phase-contrast MRI (PC-MRI) velocimetry is a noninvasive, high-resolution motion assessment tool. However, high motion sensitivity requires strong motion-encoding magnetic gradients, making phase-contrast-MRI prone to baseline shift artifacts due to the generation of eddy currents. In this study, we propose a novel nine-point balanced velocity-encoding strategy, designed to be more accurate in the presence of strong and rapidly changing gradients. The proposed method was validated using a rotating phantom, and its robustness and precision were explored and compared with established approaches through computer simulations and in vivo experiments. Computer simulations yielded a 39-57% improvement in velocity-noise ratio (corresponding to a 27-33% reduction in measurement error), depending on which method was used for comparison. Moreover, in vivo experiments confirmed this by demonstrating a 26-53% reduction in accumulated velocity error over the R-R interval. The nine-point balanced phase-contrast-MRI-encoding strategy is likely useful for settings where high spatial and temporal resolution and/or high motion sensitivity is required, such as in high-resolution rodent myocardial tissue phase mapping. Magn Reson Med, 2013. © 2012 Wiley Periodicals, Inc. Copyright © 2012 Wiley Periodicals, Inc.